Sensor Node Network Monitoring System using RESTful Web Services in Smart Farming Technology - Isnanto, Rahmat Fadli; Ubaya, Huda; Asvi, M. Fauzi; Haidar, Rosali; Sari, Purwita (Sistemasi: Jurnal Sistem Informasi, 2025)
The agricultural sector in Indonesia heavily depends on optimal environmental conditions. This study proposes a smart farming system based on the Internet of Things (IoT), utilizing RESTful web services as a more flexible and efficient IoT platform alternative. The system is designed for real-time monitoring of various environmental parameters such as temperature, air humidity, and soil conditions, including nitrogen (N), phosphorus (P), potassium (K), electrical conductivity (EC), pH, and soil moisture—captured through a network of sensor nodes. Test results show that the developed RESTful API architecture successfully facilitates effective communication between hardware and software components, enabling flexible data access and analysis through a web-based monitoring interface. This system is expected to assist farmers in making more informed decisions regarding land management, improve agricultural productivity, and support sustainable farming practices.